A draft conceptual model of SLC6A1 neurodevelopmental disorder - Goodspeed, Kimberly; Mosca, Lindsay R.; Weitzel, Nicole C.; Horning, Kyle; Simon, Elijah W.; Pfalzer, Anna C.; Xia, Maya; Langer, Katherine; Freed, Amber; Bone, Megan; Picone, Maria; Bichell, Terry Jo V. (Frontiers in Neuroscience, 2023)
SLC6A1 Neurodevelopmental Disorder (SLC6A1-NDD) is a rare syndrome caused by a mutation in the SLC6A1 gene which encodes for the GABA Transporter 1 (GAT-1) protein. GAT-1 is predominantly expressed in the nerve terminal of GABAergic interneurons as well as astrocytes and is responsible for clearing GABA from the synapse. Affected individuals typically come to medical attention with developmental delay or seizures by approximately 3 years old, and definitive diagnoses are made by identification of a variant in SLC6A1 by genetic sequencing analysis. Most disease-causing variants in SLC6A1 result in reduced function of the GAT1 transporter, leading to dysregulation of synaptic GABA levels, and likely an imbalance of excitatory and inhibitory signaling. Epilepsy is one of the most common symptoms in patients and is often the primary treatment target, though the severity of epilepsy is variable. Developmental regression has been noted by key opinion leaders and patient advocates and may be related to onset of epilepsy. Currently, no formal disease concept or disease burden study has been done. This report reflects current understanding of the disorder based upon published literature, interviews with key opinion leaders and a social media analysis of SLC6A1 support groups. In addition to seizures, patients experience motor, cognitive, communicative, behavioral, emotional, gastrointestinal, musculoskeletal and emotional disturbances with some degree of frequency. We also reviewed patient and caregiver impacts of SLC6A1-NDD and found that caregiver burden is significant, and efforts to mitigate it should be treated as a key component of managing this disorder. There is a discrepancy between the impacts of SLC6A1-NDD reported in the literature and those discussed in patient conversations, which suggests that a formal qualitative interview-based disease concept study of SLC6A1-NDD is warranted.